2020
DOI: 10.3389/fbioe.2020.551505
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Subcellular Contact Guidance on Microfabricated Substrates

Abstract: Topography of the extracellular environment is now recognized as a major biophysical regulator of cell behavior and function. The study of the influence of patterned substrates on cells, named contact guidance, has greatly benefited from the development of micro and nano-fabrication techniques, allowing the emergence of increasingly diverse and elaborate engineered platforms. The purpose of this review is to provide a comprehensive view of the process of contact guidance from cellular to subcellular scales. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 218 publications
6
82
0
Order By: Relevance
“…Filopodia have been reported as sensing organelles of the extracellular environment, playing a key role in cytoskeletal rearrangement and, subsequently, the response to topography through elongation and alignment. These observations are in line with studies carried out in other microstructured systems in which it has been observed that cells present more filopodia when cultured on structured substrates than when they are seeded on flat ones [5,[39][40][41][42][43][44][45]. For the observation of the cells under the optical microscope, as detailed in the experimental section, cells were additionally stained for non-specific proteins with Coomassie blue to enhance the contrast and better visualize cell morphology and elongation state.…”
Section: Photoembossed Cell-guiding Substratessupporting
confidence: 83%
See 1 more Smart Citation
“…Filopodia have been reported as sensing organelles of the extracellular environment, playing a key role in cytoskeletal rearrangement and, subsequently, the response to topography through elongation and alignment. These observations are in line with studies carried out in other microstructured systems in which it has been observed that cells present more filopodia when cultured on structured substrates than when they are seeded on flat ones [5,[39][40][41][42][43][44][45]. For the observation of the cells under the optical microscope, as detailed in the experimental section, cells were additionally stained for non-specific proteins with Coomassie blue to enhance the contrast and better visualize cell morphology and elongation state.…”
Section: Photoembossed Cell-guiding Substratessupporting
confidence: 83%
“…They are also used to create microlenses, waveguides, or diffractive elements to enhance the performance of photonic devices such as solar cells, liquid crystal or light-emitting 2 of 15 diode displays [1,3,4]. In the area of biomedicine, it is well recognized that surface topographic microstructures play a major role in regulating important aspects of cell behavior (migration, cell adhesion, proliferation, differentiation) and morphology, which are key to achieve functional tissue constructs for tissue regeneration and transplants, as well as the successful preparation of artificial in vitro biomimetic biological systems [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The relative modulus is mainly determined by the modulus of the bulk material unless the features are high-aspect-ratio pillars. 99–101 Surface patterning of hydrogels has been shown to alter the surface properties of hydrogel without compromising the mechanical properties. For example, flat and patterned star-shaped poly(ethylene oxide-stat-propylene oxide) hydrogel [Acr-sP(EO-stat-PO) hydrogel] samples (range of modulus 100 kPa–1 MPa) were prepared by casting from micropatterned and blank silicon masters, respectively.…”
Section: Influence Of Surface Topography or The Patterning Process On Hydrogel Mechanical Propertiesmentioning
confidence: 99%
“…36 To model these topographic cues, fibrous 2D substrates and 3D hydrogels have been used, and their effects on the cell size and shape and the 3D arrangement of the cell contact with the ECM fibres have been reported. 37 Microcontact printing is a commonly used 2D micropatterning technique that utilizes the relief patterns on a PDMS stamp to transfer adhesive proteins such as fibronectin to a substrate through conformal contact. 38 Microcontact printed arrays of fibronectin islets on PDMS surfaces were used to control the focal adhesion size that affects the α-SMA distribution in the myofibroblasts and their maturation.…”
Section: The Effect Of Topographical Cues On Myofibroblast Behavioursmentioning
confidence: 99%